ECOLOGICAL SIGNIFICANCE OF SPIDERS IN THE ECOSYSTEMS OF THE WEST KAZAKHSTAN REGION - Alibi, Kabdrakhimov (Вестник ЗКУ, 2022)
The article contains a list of numerous spider species collected in the West Kazakhstan region, 15 spider species common in the region. A brief ecological role of a number of spider species in the ecosystems of the West Kazakhstan region is presented by an annotated list. It has been established which belt the spiders belong to in the ecosystem. In addition to the popularly known krestovik spider, karakurts, mizgir, the ecology of other spiders is shown, their place in the habitat, in addition to typical herpetobionts in our region, dendro-tamnobionts and hortobionts are shown, which live covertly, not often visible to people. The trophic location of each spider species is determined and the specifics of nutrition are recorded. At the same time, the world-class area of their distribution is derived from the frequently updated world catalog of spiders and the main natural environment according to the systematized areal nomenclature is given.